The Effect of Combining Astaxanthin and Vitamin E on Neutrophils, Leukocytes, and Platelet Counts - Sampurna Sampurna; Rita Kartika Sari; Herliana Junita; Nafisa Yasmin Suseno; Salsabila Tria Ramadhani (GLOBAL HEALTH SCIENCE GROUP, 2026)
Inflammation is a defensive response that eliminates lesions caused by injury and can be induced by 1% carrageenan, leading to increased blood neutrophil, leukocyte, and platelet counts. Astaxanthin and vitamin E are antioxidants with potential anti-inflammatory properties; however, the effects of their combination remain underexplored. This study evaluates the impact of combined astaxanthin and vitamin E administration on neutrophil, leukocyte, and platelet counts in white male Wistar rats using a carrageenan-induced inflammation model with a Post Test Only Control Group Design. Thirty white male Wistar rats were selected using a simple random sampling method and randomly assigned into three groups: KN (normal), KS (disease, induced with 1% carrageenan), and KP (treatment, receiving astaxanthin 0.72 mg/kgBW and vitamin E 24.1 mg/kgBW with 1% carrageenan). Following treatment, neutrophil, leukocyte, and platelet counts were measured using a hematology analyzer and subjected to normality and homogeneity testing, followed by parametric and nonparametric analyses with post hoc testing. The results show that combining astaxanthin and vitamin E has an anti-inflammatory effect by lowering neutrophil, leukocyte, and platelet counts in carrageenan-induced male Wistar rats.